2019
DOI: 10.3390/molecules24213935
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Physicochemical, Bioactive Compounds and Antioxidant Capacity during the Brewing Process of Zhenjiang Aromatic Vinegar

Abstract: Zhenjiang aromatic vinegar (ZAV) is a kind of traditional fermented food worldwide. In this study, the changes of physicochemical properties, total phenolic content (TPC), total flavonoid content (TFC), and total antioxidant activity (TAA) were evaluated during the brewing process of ZAV. In addition, the correlation between phenolic compound contents and antioxidant activities was investigated during the aging process (AP) of ZAV. The results showed that total acids, non-volatile acids, and amino nitrogen inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
4
17
1
Order By: Relevance
“…During the brewing process, aromatic vinegar produces many bioactive compounds, such as organic acids, amino acids and phenolic compounds, which play important roles in antioxidant activities (Zhang et al, 2019). In addition, polyphenols, flavonoids, and melanoidins were found in Hengshun aromatic vinegar, which play crucial roles in diseases prevention and contribute benefits to human health (Zhao et al, 2018;Duan et al, 2019). Studies have also showed that the alkylpyrazine named ligustrazine was found as a bioactive compound in Hengshun aromatic vinegar, which has the health effects such as reducing blood pressure, promoting blood circulation and removing stasis, improving coronary heart disease, thrombolytic therapy and liver protection (Xu et al, 2011b;Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the brewing process, aromatic vinegar produces many bioactive compounds, such as organic acids, amino acids and phenolic compounds, which play important roles in antioxidant activities (Zhang et al, 2019). In addition, polyphenols, flavonoids, and melanoidins were found in Hengshun aromatic vinegar, which play crucial roles in diseases prevention and contribute benefits to human health (Zhao et al, 2018;Duan et al, 2019). Studies have also showed that the alkylpyrazine named ligustrazine was found as a bioactive compound in Hengshun aromatic vinegar, which has the health effects such as reducing blood pressure, promoting blood circulation and removing stasis, improving coronary heart disease, thrombolytic therapy and liver protection (Xu et al, 2011b;Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in physicochemical properties, TPC, TFC, and AC of the traditional ZAV during its brewing process were also evaluated by Duan et al [ 31 ], and the correlation between the TPC and AC was investigated. The results show that total acids, non-volatile acids, and amino nitrogen increased during the brewing process, while TPC, TFC, and AC were kept at low levels during alcoholic fermentation and reached their highest levels at the 6th year of aging.…”
Section: Health Benefits Of Cereal Vinegarsmentioning
confidence: 99%
“…Catechin, vanillic acid, and syringic acid contributed more during the aging process. According to these findings, it was concluded that the quality and functional properties of ZAV could be controlled [ 31 ].…”
Section: Health Benefits Of Cereal Vinegarsmentioning
confidence: 99%
“…Ultraviolet-visible spectroscopy is generally employed to elucidate several functional groups and perform their quantifications based on its absorption or reflectance in the UV-vis range. The Folin-Ciocalteu approach is commonly used to determine the TPC concentration in different types of samples, such as in vinegar [51], raspberry [47], aloe vera [52], rice [53], and açai [10] among others.…”
Section: Introductionmentioning
confidence: 99%